The Prevalence of Intimate Partner Violence and Association With Depression in University Students: Results of a Cross-Sectional Study. Issue 1 (January 2021) - Musa, Arif; Valdez, Alfonso J.; Aguilar, Jose L.; Pendi, Kasim; Wolitzky-Taylor, Kate B.; Lee, Danny; Lee, Joshua; Safani, David
Abstract : Abstract: The purpose of this cross-sectional study was to determine the prevalence of intimate partner violence (IPV) among university students, investigate the potential predictors of IPV in this population, and study the link between IPV and depression. The survey included sociodemographic, relationship quality, and depression-related questions. From 498 respondents, the prevalence of IPV was 4.8%, depression was 30.9%, and suicidal ideation was 20.3%. After adjusting for covariates and confounders, relationship satisfaction (odds ratio [OR], 0.201; 95% confidence interval [CI], 0.101–0.401; p < 0.001) and jealousy (OR, 0.270; 95% CI, 0.094–0.776; p = 0.015) were significant predictors of IPV. Relationship satisfaction predicted depressive disorders (OR, 0.504; 95% CI, 0.365–0.698; p < 0.001). IPV trended toward predicting the presence of a depressive disorder (OR, 0.436; 95% CI, 0.170–1.113; p = 0.083). Relationship satisfaction and jealousy predicted IPV. Although IPV did not predict depression, poor relationship satisfaction increased the odds of depression, implicating the influence of relationship satisfaction on both IPV and depression.